Draft Annual Plan 1987-88 Volume II Government of Bihar - Planning Commission (Planning Commission, 1987)
Agricultural Education and Research, Crop Husbandry, Lac Development, Sugarcane Development, Agricultural Marketing, Storage and Warehousing, Special Programmes for Development, (a) Drought prone Area Programme, (b) National Rural Employment Programme (c) Integrated Rural Development.
Planning Department